Evaluación de la estabilidad fisicoquímica y microbiológica de un extracto acuoso de moringa (Moringa oleífera Lam), cosechada en la Facultad de Ciencias Agropecuarias de la Universidad Técnica de Machala - Pulla Marca, Hugo M. (2014)
Physical stability, microbiological and quantitative chemistry of an aqueous extract from the leave of Moringa oleífera were evaluated, considering storage conditions: temperature, light and types of packaging.